2003
DOI: 10.1021/cm0304039
|View full text |Cite
|
Sign up to set email alerts
|

Reinvestigation of the Layered Double Hydroxide Containing Tetravalent Cations: Unambiguous Response Provided by XAS and Mössbauer Spectroscopies

Abstract: The incorporation of tetravalent cations (Zr 4+ and Sn 4+ ) inside sheets of layered double hydroxide (LDH) was reported by Velu et al. As no local structural information was provided so far, the question here is whether the LDH structure may accommodate such a presence. From three different systems presenting the cation compositions MgAlSn, MgAlZr, and CoAlSn, we provide (by means of X-ray absorption and Mo ¨ssbauer spectroscopies) clear evidence that the tetravalent cations are segregated from the LDH struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 35 publications
3
34
0
3
Order By: Relevance
“…in Leroux et al, 2001;Intissar et al, 2003;Forano et al, 2006), including in two highly cited reviews (Cavani et al, 1991;Evans & Slade, 2006); the error is the omission of r(OH À ) from the equation [cf. equation (3)].…”
Section: Layered Double Hydroxidesmentioning
confidence: 99%
“…in Leroux et al, 2001;Intissar et al, 2003;Forano et al, 2006), including in two highly cited reviews (Cavani et al, 1991;Evans & Slade, 2006); the error is the omission of r(OH À ) from the equation [cf. equation (3)].…”
Section: Layered Double Hydroxidesmentioning
confidence: 99%
“…Some of studies reported the possibility of synthesizing LDHs containing M(IV) ions [5,[19][20][21][22][23][24]. Another authors based on results of X-ray absorption spectroscopy (XAS) and Mössbauer spectroscopy [25] concluded that the M(IV) cations are segregated from LDH structure and may form amorphous M(IV) oxide-like particles. In our study the main reason to investigate the possibility of Zr-containing LDH formation was the expectation that the incorporation of tetravalent cation has to affect on anion-exchange properties of LDHs due to the change of positive charge in brucite-like layers.…”
Section: Introductionmentioning
confidence: 99%
“…After this, the syntheses of other similar systems (NiAlSn, CoAlSn) were also reported by this group [39] [40] . Soon after that, another group [41] [42] embarked on studying this topic again, and attempted the synthesis of Mg(II)Al(III)Sn(IV)-LDH with the method given earlier [38] and for characterization, 119 Sn Mössbauer and X-ray absorption spectroscopies were applied. It was found that the tetravalent cations were not incorporated in the layers of the LDH, instead, they formed M(IV) oxide-like particles, which were segregated from the layers.…”
Section: Aluminum- Iron-and Tin-based Layered Double Hydroxidesmentioning
confidence: 99%